SIG BERBASIS GOOGLE MAPS API TERINTEGRASI SMS GATEWAY UNTUK MEMANTAU KEGIATAN KKN - Agung, I Putu Suhada; Hudoyo, Sapto Hudoyo (Acintya, 2018)
This research is motivated by the difficulties in monitoring the implementation of Lecture of Real Work Lecture/Kuliah Kerja Nyata (KKN). Google Maps digital map application owned by Google is integrated with SMS input data from each KKN service post with various information. This system design method is to conduct initial study problems in the field, observation and literature study as well as interviews about system requirements made. Interviews were conducted to those related to KKN activities, including Coordinator and field supervisor/Dosen Pembimbing Lapangan(DPL) KKN. Research data is used to get the system needs made related to SMS input data, SMS data format, and display, as well as technical data in the field, including signal coverage and cell phone signal strength. From the data collected, it is analyzed to apply Geographic Information System (GIS) based on SMS Gateway to monitor KKN activities in real time. The use of SMS is chosen with consideration of the presence of stronger 2G (phone and SMS) signals than 3G and 4G signals (Internet data signals) in remote locations. The SMS format used is: KKN # LOCATION # INFORMATION. GIS is displayed in the form of markers andÂ  windows information on the Google Maps map containing information that may change according to the content of the SMS sent from each KKN post. Furthermore the system is tested to determine the response to data sent via SMS.Â Keywords: KKN, GIS, SMS.